Re-emergence of Western equine encephalitis virus (WEEV) in Argentina in 2023-2024 (Actualizaciones en Sida e Infectología, 2024)
Intense epizootics have been identified in the temperate area of Argentina for Western equine encephalitis virus (WEEV) since at least 1908. In 1933, the first WEEV strain was isolated from a sick equine in Buenos Aires. From then until 1982-1983, epizootics occurred in Buenos Aires, Córdoba, Santa Fe, Santiago del Estero, Chaco and Río Negro. The eco-epidemiological studies of those years also made it possible to detect and characterize WEEV strains in enzootic foci from mosquitoes and to determine differences in virulence, aspects that positioned our country as one of the areas in Latin America with the greatest coverage of viral characterization studies. Fewer than ten human cases of WEEV have been detected in relation to these events in the past and, strikingly, they come from the Southern end of the epizootic areas (Rio Negro). Other Alphaviruses identified in Argentina are Aura virus, Eastern equine encephalitis, Venezuelan equine encephalitis, and Una virus. Finally, more recently and with greater impact on public health, the Chikungunya virus. However, this viral family has not been one of the most circulating arboviruses in recent decades in the country, which have been marked by an increase in the activity of Flaviviruses.For this reason, the National Service of Agrifood Health and Quality (SENASA) alert issued on November 25 of 2023, due to positive results for Alphavirus in equines with neurological symptoms in the central region of Argentina, was a cause for concern. Within one week, three virology institutions -the Virology Institute José María Vanella (of the UNC), the Virology Institute of the Center for Research in Veterinary and Agronomic Sciences (CICVyA) (of the INTA) and the National Institute of Human Viral Diseases Dr. Julio I. Maiztegui (INEVH) (of the ANLIS)- were able to identify the viral agent by viral family generic molecular methodologies and confirm the identity by genomic sequencing of the amplified fragments, as well as validate these results by real-time PCR methodologies with WEEV-specific probes and primers. Since then, as of March 7, 2024, SENASA has confirmed a total of 1466 WEEV outbreaks in equines in 16 provinces.In this new epizootic context, since the intensification of human surveillance in November 2023 and up to the epidemiological week (EW) 10 of 2024, 418 suspected cases have been reported in 16 provinces, with 114 laboratory-positive cases, including confirmed and probable cases.What has changed? Is it just a matter of favorable vector and environmental conditions? Are there socioeconomic and lifestyle changes that lead the population to higher exposure at the urban-rural interface with increased exposure in the wild? Is it an increased occurrence of human cases due to some viral characteristic? Has this virus been recently introduced from the Northern hemisphere or is it the emergence of a viral variant maintained in local enzootic foci? Are there improvements in the surveillance system and greater sensitivity for clinical detection of compatible cases? Are there better methodologies for etiological identification of WEEV infection? These and other questions challenge today's knowledge and understanding of this viral emergency we are going through in Argentina, Uruguay and Brazil.Regarding the epidemiological surveillance of human cases, it is noteworthy that the intersectoral work between SENASA and the areas of epidemiology, zoonosis and vector control of the National Ministry of Health (MSN) allowed strengthening the "One Health" approach and without delays, the day after SENASA communicates the WEEV epizootic, the MSN issues an epidemiological alert with recommendations for the health team, establishing: surveillance modality, definition of suspected case, actions aimed at etiological diagnosis and guidelines for control and prevention.The etiological diagnosis of this arbovirus faces the challenge of not having commercial supplies available in the market due to its low global incidence. On the other hand, since man is a terminal host with the development of low-magnitude viraemia, the diagnostic strategy is mostly successful when serological methods are applied. From viral strains of the epizootic years kept in the institutional strain stock at the National Reference Center (INEVH), batches of antigens were produced and the MAC-ELISA IgM methodology was developed. On the other hand, the use of neutralization in cell cultures for the Alphavirus panel is proposed as a method of serological confirmation and positive controls are generated for molecular methods, the laboratory algorithm is established and rapid access to virological diagnosis is provided in human cases with compatible clinical symptoms. Criteria are established for the referral of samples from the national network laboratories for arbovirus diagnosis and it is proposed, initially, to maintain centralized diagnosis as a strategy to optimize the use of available reagents. This activation and response of the system to the alert generated by the epizootic made it possible for the country to confirm a first human case of this virus by December 20, 2023, and to characterize the current outbreak as one of the highest in terms of impact and human infection detected to date.The equines played the role of sentinels marking areas with viral circulation where surveillance, prevention and control could be strengthened. The implementation of compulsory vaccination has made it possible to reduce the incidence of the disease in this component and marks the current need to be very alert to compatible clinical cases in people who may or may not have an epidemiological link with epizootics. Western equine encephalitis is a re-emerging disease due to its periodic impact and occasional occurrence of outbreaks of varying magnitude. As current experience has shown, virus activity can fluctuate over time, influenced by factors such as climate conditions, mosquito vector distribution, and intermediate host and reservoir dynamics. Due to the lack of active and systematic surveillance in most countries in the region, together with the fact that WEEV symptoms in humans may not be recognized, there is low case detection and difficulties in diagnosis, which underestimates the true burden of the disease. Strengthening the actions of institutions with installed capacities to lead virological studies and promote the performance of ecological studies will be of relevance for a complete characterization of the vectors and reservoirs involved in transmission, as well as to answer the various questions posed by the current reemergence of WEEV.
Keywords: WEEV; Western equine encephalitis virus